The microRNA-451a/chromosome segregation 1-like axis suppresses cell proliferation, migration, and invasion and induces apoptosis in nasopharyngeal carcinoma. Issue 1 (1st January 2021) - Luo, Yi; Qu, Xiu; Kan, Dan; Cai, Binlin
ABSTRACT: MicroRNA-451a (miR-451a) has been implicated in the initiation and progression of multiple cancers. However, the regulatory mechanisms underlying its function in nasopharyngeal carcinoma (NPC) are poorly understood. Thus, we investigated in detail the role of the microRNA-451a/chromosome segregation 1-like (miR-45a/CSE1L) axis and its regulatory mechanism in NPC. We examined the levels of miR-451a and CSE1L in NPC, and assessed the effects of miR-451a and CSE1L on NPC by cell functional experiments. Furthermore, we elucidated the direct regulatory effect of miR-451a on CSE1L by the luciferase reporter assay, RNA pull-down assay, and RNA immunoprecipitation and validated our observations by calculating the Pearson's correlation coefficient. We found that miR-451a was down-regulated in NPC cells, and its over-expression attenuated cell proliferation, migration, and invasion, and tumor growth in 5–8 F and SUNE-1 cells and promoted apoptosis. Moreover, CSE1L was the direct gene target of miR-451a, and its over-expression abrogated miR-451a-dependent inhibition of malignancy in 5–8 F and SUNE-1 cells. The Pearson's correlation coefficient indicated a negative correlation between CSE1L and miR-451a. miR-451a serves as a tumor suppressor and targets CSE1L . miR-451a suppresses CSE1L expression, thereby reducing proliferation, invasion, and migration and increasing apoptosis of NPC cells.